Secondary battery, positive electrode active material, and electric device
Patent Information
- Application Number
- CN202510475342.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-15
- Publication Date
- 2026-10-23
AI Technical Summary
在二次电池的充放电过程中,尖晶石结构富锰材料等正极活性材料溶出锰离子,会快速沉积到负极极片的固体电解质界面(solid electrolyte interphase,SEI)膜,而对固体电解质界面膜产生破坏,降低二次电池的电化学性能
[0031]上述说明仅是本申请技术方案的概述,为了能够更清楚了解本申请的技术手段,而可依照说明书的内容予以实施,并且为了让本申请的上述和其它目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。
Smart Images

Figure CN122968255A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy technology, and in particular to lithium-ion secondary batteries, positive electrode active materials and electrical equipment. Background Technology
[0002] Secondary batteries possess high energy density and are widely used in wireless communication, transportation, aerospace, and other fields. During the charging and discharging process of secondary batteries, manganese ions dissolve from the positive electrode active materials, such as spinel-structured manganese-rich materials, and rapidly deposit onto the solid electrolyte interphase (SEI) film of the negative electrode, damaging the SEI film and reducing the electrochemical performance of the secondary battery. The above statements are for providing background information related to this application only and do not necessarily constitute prior art. Summary of the Invention
[0003] The main technical problem addressed by this application is to provide a secondary battery, a positive electrode active material, and an electrical device that can improve the dissolution of manganese ions, slow down the capacity decay of the secondary battery, and improve the storage performance of the secondary battery.
[0004] To address the aforementioned technical problems, this application provides a secondary battery, comprising a positive electrode, a negative electrode, and an electrolyte. The positive electrode comprises a positive active material, which includes a core and a surface layer. The core comprises a first spinel-type material containing manganese, wherein the molar percentage of manganese in the first spinel-type material is R1, where R1 is greater than or equal to 0.1 and less than or equal to 0.4. The surface layer covers or adheres to the outer surface of the core, and the surface layer comprises a second spinel-type material, wherein the molar percentage of manganese in the second spinel-type material is R2, where R2 is greater than or equal to 0 and less than R1.
[0005] In this embodiment, the first spinel material contains manganese. A second spinel material is coated or attached to the surface of the first spinel material. The second spinel material has the same crystal form as the first spinel material, and their surface tensions are similar. This allows the second spinel material to coat or attach to the surface of the first spinel material more uniformly and densely. The molar percentage R2 of manganese in the second spinel material is less than that in the first spinel material. The molar percentage of manganese in the material is R1. The stability of the second spinel material is greater than that of the first spinel material. This allows the second spinel material to protect the first spinel material, reducing the probability of the first spinel material coming into contact with electrolytes such as the electrolyte, reducing the probability of manganese from the first spinel material dissolving into the electrolyte, reducing the amount of manganese deposited on the SEI film surface of the negative electrode, reducing damage to the SEI film, improving the capacity decay of the secondary battery, and enhancing the storage performance of the secondary battery.
[0006] In any embodiment, the sum of the molar percentages of nickel and manganese in the first spinel material is R3, where R3 is greater than or equal to R1; the sum of the molar percentages of nickel and manganese in the second spinel material is R4, where R4 is greater than or equal to R2 and less than R3. In this embodiment, during the charging and discharging process of the secondary battery, when fully charged, the nickel in the positive electrode active material exhibits a +4 oxidation state, resulting in strong oxidizing properties and a tendency to undergo side reactions with the electrolyte. In this embodiment, by controlling the sum of the molar percentages of nickel and manganese in the second spinel material to be less than that of the first spinel material (i.e., R4 < R3), the second spinel material exhibits stronger stability and lower oxidizing properties during full charge compared to the first spinel material. This protects the first spinel material, reduces the probability of side reactions between the positive electrode active material and the electrolyte, improves the capacity retention rate of the secondary battery, and enhances its storage performance.
[0007] In any embodiment, the first spinel-type material comprises Li x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1The material has the following properties: 0.9≤x1≤1.2, 0≤y1≤0.3, 0.9≤x1+y1≤1.2, 1≤r1≤2, 0≤d1≤0.6, -0.1≤k1≤0.5, 0≤δ1≤0.5; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Me includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Cr, B, Al, Ga, In, Sc, Ti, V, Mn, Fe, Co, Y, Zr, Nb, Mo, Pb, Ta, W, lanthanides, C, Si, Ge, Sn, Pb, Sb, Bi, Te, P, and S; G includes one or more of F, Cl, Br, and I. In this application embodiment, the first spinel-type material includes the material with the above-mentioned chemical formula, which has the characteristics of high energy density and excellent high-rate charge-discharge performance.
[0008] In any embodiment, the second spinel-type material includes the chemical formula Li x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The materials are 0≤x²≤2, 0≤y²≤2, 0.9≤x²+y²≤2, 0≤r²<2, 0≤d²≤0.6, 0≤a²≤2, 0≤b²≤2, 0≤r²<2, -0.1≤k²≤0.5, 0≤δ²≤2; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Ma includes one or more of Cr, Sc, V, Fe, Co, and Ni; Mb includes one or more of B, Al, Ti, Zr, Nb, Mo, Ta, W, Ce, Si, Te, and P; Mc includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Ga, In, Y, Pb, lanthanides, C, Ge, Sn, Pb, Sb, Bi, and S; G includes one or more of F, Cl, Br, and I. In this embodiment, the second spinel-type material includes materials with the aforementioned chemical formula, resulting in higher structural stability, lower oxidation resistance, and higher acid resistance, thus enabling the second spinel-type material to protect the first spinel-type material. In this embodiment, the element contained in Mb can stabilize the oxygen element in the spinel structure, improving the stability of the second spinel-type material.
[0009] In any implementation, r2 < r1. In the embodiments of this application, the chemical formula Li...x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The subscript r2 of manganese in the formula Li is less than that in the chemical formula Li. x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1 The subscript r1 for manganese in the second spinel material results in a lower molar ratio of manganese in the second spinel material compared to the first spinel material. This makes the second spinel material more stable than the first, allowing it to protect the first spinel material. This reduces the probability of the first spinel material coming into contact with electrolytes such as the electrolyte, reduces the probability of manganese leaching from the first spinel material into the electrolyte, reduces the amount of manganese deposited on the SEI film surface of the negative electrode, reduces damage to the SEI film, improves the capacity decay of the secondary battery, and enhances the storage performance of the secondary battery.
[0010] In any embodiment, r2+d2 < r1+d1. In the embodiments of this application, the chemical formula Li... x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The sum of the subscripts of manganese and Ni in the chemical formula Li is less than that in Li. x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1 The sum of the subscripts of manganese and nickel in the second spinel material makes the total molar ratio of manganese and nickel in the second spinel material less than that in the first spinel material. This results in the second spinel material being more stable and less oxidizable when fully charged compared to the first spinel material. It can protect the first spinel material, reduce the probability of side reactions between the positive electrode active material and the electrolyte, improve the capacity retention rate of the secondary battery, and enhance the storage performance of the secondary battery.
[0011] In any embodiment, 0 ≤ r2 < 1. In the embodiments of this application, by controlling r2 within the above range, that is, the subscript of manganese in the second spinel material is less than 1 and greater than or equal to 0, the content of manganese in the second spinel material is relatively small. This is beneficial to reducing the probability of manganese dissolution in the second spinel material, which is beneficial to reducing the catalytic activity of the second spinel material, reducing the probability of the second spinel material catalyzing the electrolyte reaction, and improving the capacity retention rate of the secondary battery.
[0012] In any embodiment, 0 ≤ a2 ≤ 1. In the embodiments of this application, Ma contains elements with high activity. By controlling the subscript a2 of Ma to be less than or equal to 1 and greater than or equal to 0, the content of highly active elements is reduced, which is beneficial to reduce the catalytic activity of the second spinel material, reduce the probability of the second spinel material catalyzing the electrolyte reaction, and improve the capacity retention rate of the secondary battery.
[0013] In any embodiment, 0 < x2 ≤ 1.2. In the embodiments of this application, x2 is within the above range, which allows the second spinel-type material to contain lithium ions as active ions, enabling the active ions to migrate rapidly on the surface and exhibiting better kinetic performance, which is beneficial for the secondary battery to have fast charge and discharge performance.
[0014] In any embodiment, 1 ≤ b2 ≤ 2. In the embodiments of this application, by controlling the subscript b2 of Mb within the above range, the subscript of Mb is made larger, resulting in a higher Mb element content in the second spinel material. This can stabilize the oxygen element in the spinel structure, which is beneficial to improving the structural stability of the second spinel material, improving the stability of the positive electrode active material, reducing the probability of side reactions between the positive electrode active material and the electrolyte, and improving the capacity retention rate of the secondary battery.
[0015] In any embodiment, Mb includes one or more of Zr, Nb, Mo, Ta, Te, and P. In the embodiments of this application, Mb includes one or more of the above elements, which can better stabilize the oxygen element in the second spinel-type material, improve the stability of the second spinel-type material, improve the stability of the positive electrode active material, and help improve the capacity retention rate of the secondary battery.
[0016] In any embodiment, the first spinel-type material includes one or more of lithium manganese oxide, lithium nickel manganese oxide, lithium nickel iron manganese oxide, lithium nickel iron aluminum niobium manganese oxide, and lithium nickel copper iron aluminum niobium manganese oxide. The second spinel-type material includes one or more of lithium nickel manganese oxide, lithium iron manganese oxide, lithium iron aluminum niobium titanium manganese oxide, lithium iron zirconium antimony manganese oxide, lithium aluminum niobium titanium manganese oxide, lithium cobalt aluminum niobium titanium manganese oxide, lithium iron aluminum niobium titanium manganese oxide, lithium magnesium aluminum niobium titanium manganese oxide, lithium copper titanium manganese oxide, magnesium iron manganese aluminum titanium oxide, lithium magnesium aluminum antimony oxide, and magnesium aluminum oxide. In the embodiments of this application, the first spinel-type material and the second spinel-type material respectively include the above-mentioned materials. The second spinel-type material coats or adheres to the surface of the first spinel-type material, resulting in lower catalytic activity and lower oxidizability of the positive electrode active material, acid resistance, stronger stability of the positive electrode active material, better capacity retention rate of the secondary battery, and better storage performance of the secondary battery.
[0017] In any embodiment, the surface layer comprises a non-spinel material, which includes one or more of inorganic substances with melting points below 1000°C, glucose, sucrose, fructose, amorphous carbon, and organic polymers. In embodiments of this application, the surface layer further comprises a non-spinel material, which, when mixed with a second spinel material, can disperse the second spinel material, resulting in a more uniform dispersion and improving the density of the surface layer coating or adhering to the surface of the first spinel material.
[0018] In any embodiment, the inorganic material with a melting point below 1000°C includes one or more of lithium phosphate, lithium borate, boric acid, vanadium pentoxide, and boron oxide. In this application embodiment, lithium phosphate can suppress the dissolution of manganese ions in the first spinel-type material and simultaneously improve lithium-ion conductivity. Coating or attaching lithium phosphate can improve the density of the surface layer. Boric acid and lithium borate can suppress the dissolution of manganese ions. Lithium borate can improve the compatibility between the electrolyte and the positive electrode active material, reduce side reactions between the positive electrode active material and the electrolyte, and improve the capacity retention rate of the secondary battery. Vanadium pentoxide can improve electronic conductivity, reduce resistance, participate in the formation of the SEI film, and improve the density of the surface layer coated or attached to the first spinel-type material. Boron oxide can enhance the structural stability of the positive electrode active material and improve the capacity retention rate of the secondary battery.
[0019] In any embodiment, the organic polymer includes one or more of polyacrylic acid, lithium polyacrylate, cyclohexanehexaphosphate, and phenolic resin. In this embodiment, the organic polymer can disperse the second spinel-type material, improving the density of the coating or attachment on the surface of the first spinel-type material. Specifically, polyacrylic acid can reduce the erosion of the first spinel-type material by the electrolyte and reduce the dissolution of manganese ions from the first spinel-type material. Lithium polyacrylate can act as a lithium-ion conductor, mixing with the second spinel-type material to coat or attach to the surface of the first spinel-type material, enhancing the ion contact between the positive electrode active material and the electrolyte, and participating in the formation of the SEI film, reducing side reactions and improving electrochemical performance. The multiple phosphate groups in cyclohexanehexaphosphate can chelate with metallic manganese ions, reducing the reach of manganese ions from the positive electrode active material to the SEI film of the negative electrode, reducing the damage to the SEI film layer by manganese ions, and improving the capacity retention rate of the secondary battery. Phenolic resin is mixed with a second spinel-type material to coat or attach to the outer surface of the first spinel-type material, which can form a dense surface layer, reduce the probability of direct contact between the first spinel-type material and the electrolyte, and improve the stability of the positive electrode active material.
[0020] In any embodiment, the mass ratio of the non-spinel material to the second spinel material is greater than or equal to 0 and less than or equal to 2. In this embodiment, by controlling the mass ratio of the non-spinel material to the second spinel material within the above range, the non-spinel material can disperse the second spinel material, improving the uniformity of the second spinel material in the surface layer and increasing the density of the coating or attachment on the surface of the first spinel material. The coating or attachment of the second spinel material to the surface of the first spinel material can protect the first spinel material. Simultaneously, the second spinel material can provide ion transport channels, facilitating the transport of active ions and improving the capacity retention rate of the secondary battery.
[0021] In any embodiment, the mass ratio of the non-spinel material to the second spinel material is greater than or equal to 0.1 and less than or equal to 1. In the embodiments of this application, the mass ratio of the non-spinel material to the second spinel material is within the above range, which makes the proportion of the second spinel material in the surface layer better, which is beneficial to protect the first spinel material and improve the capacity retention rate of the secondary battery.
[0022] In any embodiment, the surface layer accounts for 0.01% to 30% of the total mass of the positive electrode active material. In the embodiments of this application, by controlling the mass percentage of the surface layer within the above range, a uniform coating or adhesion layer can be formed on the surface of the first spinel-type material, while simultaneously enabling the positive electrode active material to have better electrochemical performance.
[0023] In any embodiment, the volume average particle size D of the positive electrode active material is... V 50 represents the particle size range of 1 μm to 50 μm. In the embodiments of this application, the volume average particle size D of the positive electrode active material is... V Within the above range, 50 results in the positive electrode sheet having high compaction density and mechanical strength, which is beneficial for the secondary battery to have high energy density.
[0024] The second aspect of this application includes a positive electrode active material, comprising a core and a surface layer. The core comprises a first spinel-type material containing manganese, wherein the molar percentage of manganese in the first spinel-type material is R1, and R1 is greater than or equal to 0.1 and less than or equal to 0.4. The surface layer covers or adheres to the outer surface of the core, and the surface layer comprises a second spinel-type material, wherein the molar percentage of manganese in the second spinel-type material is R2, and R2 is greater than or equal to 0 and less than R1.
[0025] The positive electrode active material in this application includes a core containing a first type of spinel material and a surface layer containing a second type of spinel material. The second type of spinel material has the same crystal form and similar surface tension as the first type of spinel material. By coating or attaching the second type of spinel material to the outer surface of the first type of spinel material, the second type of spinel material can be uniformly and densely coated or attached to the surface of the first type of spinel material. The molar ratio R2 of manganese element in the second type of spinel material is less than the molar ratio R1 of manganese element in the first type of spinel material. The stability of the second type of spinel material is greater than that of the first type of spinel material. This allows the second type of spinel material to protect the first type of spinel material, reduce the amount of manganese dissolved from the first type of spinel material, and improve the stability of the positive electrode active material.
[0026] In any embodiment, the sum of the molar percentages of nickel and manganese in the first spinel material is R3, where R3 is greater than or equal to r1; the sum of the molar percentages of nickel and manganese in the second spinel material is R4, where R4 is greater than or equal to R2 and less than R3. In this embodiment, by controlling the sum of the molar percentages of nickel and manganese in the second spinel material to be less than that in the first spinel material (i.e., R4 < R3), the second spinel material exhibits stronger stability and lower oxidizability than the first spinel material when fully charged in a secondary battery. This protects the first spinel material, reduces the probability of side reactions between the positive electrode active material and the electrolyte, and improves the capacity retention rate of the positive electrode active material.
[0027] In any embodiment, the first spinel-type material comprises Li x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1 The material has the following properties: 0.9≤x1≤1.2, 0≤y1≤0.3, 0.9≤x1+y1≤1.2, 1≤r1≤2, 0≤d1≤0.6, -0.1≤k1≤0.5, 0≤δ1≤0.5; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Me includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Cr, B, Al, Ga, In, Sc, Ti, V, Mn, Fe, Co, Y, Zr, Nb, Mo, Pb, Ta, W, lanthanides, C, Si, Ge, Sn, Pb, Sb, Bi, Te, P, and S; G includes one or more of F, Cl, Br, and I. In the embodiments of this application, the first spinel-type material includes the material with the above chemical formula, which makes the positive electrode active material have a high energy density.
[0028] In any embodiment, the second spinel-type material includes the chemical formula Li x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2The materials are 0≤x²≤2, 0≤y²≤2, 0.9≤x²+y²≤2, 0≤r²<2, 0≤d²≤0.6, 0≤a²≤2, 0≤b²≤2, 0≤r²<2, -0.1≤k²≤0.5, 0≤δ²≤2; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Ma includes one or more of Cr, Sc, V, Fe, Co, and Ni; Mb includes one or more of B, Al, Ti, Zr, Nb, Mo, Ta, W, Ce, Si, Te, and P; Mc includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Ga, In, Y, Pb, lanthanides, C, Ge, Sn, Pb, Sb, Bi, and S; G includes one or more of F, Cl, Br, and I. In this embodiment, the second spinel-type material includes materials with the aforementioned chemical formula, resulting in better structural stability, lower oxidation resistance, and higher acid resistance, thus enabling the second spinel-type material to protect the first spinel-type material. In this embodiment, the element contained in Mb can stabilize the oxygen element in the spinel structure, improving the stability of the second spinel-type material.
[0029] In any embodiment, the surface layer comprises a non-spinel material, which includes one or more of inorganic substances with melting points below 1000°C, glucose, sucrose, fructose, amorphous carbon, and organic polymers. In embodiments of this application, the surface layer further comprises a non-spinel material, which, when mixed with a second spinel material, can disperse the second spinel material, resulting in a more uniform dispersion and improving the density of the surface layer's coating or adhesion to the surface of the first spinel material.
[0030] A third aspect of this application includes an electrical device comprising a secondary battery as described in the first aspect, and / or a positive electrode active material as described in the second aspect. The electrical device in the embodiments of this application has the secondary battery of the first aspect and / or the positive electrode active material of the second aspect, possessing the same advantages as the secondary battery of the first aspect and / or the same advantages as the positive electrode active material of the second aspect.
[0031] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0032] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0033] Figure 1 This is a schematic diagram of the structure of a vehicle according to one or more embodiments;
[0034] Figure 2 This is an exploded structural diagram of a battery according to one or more embodiments;
[0035] Figure 3 This is an exploded structural diagram of a battery cell according to one or more embodiments;
[0036] Figure 4a The C 1s spectra were obtained from the X-ray photoelectron spectroscopy of Example 1, Comparative Example 1, and Comparative Example 2.
[0037] Figure 4b The Mn 2p spectra were obtained from the X-ray photoelectron spectroscopy of Example 1, Comparative Example 1, and Comparative Example 2.
[0038] Figure 4c The Fe 2p spectra were obtained from the X-ray photoelectron spectroscopy of Example 1, Comparative Example 1, and Comparative Example 2.
[0039] Figure 5a The image shows a scanning electron microscope image of the positive electrode active material in Comparative Example 1.
[0040] Figure 5b This is a scanning electron microscope image of the positive electrode active material in Comparative Example 2.
[0041] Figure 5c This is a scanning electron microscope image of the positive electrode active material of Example 1;
[0042] Figure 6a Transmission electron micrograph of the positive electrode active material in Example 1;
[0043] Figure 6b This is a local cross-sectional energy dispersive spectrum of the positive electrode active material in Example 1.
[0044] In the attached image:
[0045] 1000, Vehicle; 300, Motor; 200, Controller; 100, Secondary Battery; 10, Housing; 11, First Part; 12, Second Part; 20, Battery Cell; 21, End Cap; 21a, Electrode Terminal; 22, Housing; 23, Electrode Assembly. Detailed Implementation
[0046] To make the objectives, technical solutions, and effects of this application clearer and more explicit, the embodiments of the technical solutions of this application will be described in detail below with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solutions of this application, and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0048] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces), unless otherwise explicitly specified.
[0049] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0050] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0051] Quantities, ratios, and other numerical values are presented in range format in this document. It should be understood that this range format is for convenience and brevity and should be interpreted flexibly to include not only numerical values explicitly specified as range limits, but also all individual numerical values or subranges covered within the range, as if each numerical value and subrange were explicitly specified.
[0052] Unless otherwise specified, all steps of this application may be performed sequentially, randomly, or in parallel, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially, or steps (a) and (b) may be performed simultaneously in parallel. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or steps (a), (c), and (b), or steps (c), (a), and (b), etc.
[0053] In manganese-containing positive electrode active materials such as spinel-structured manganese-rich materials, manganese (Mn) is unstable and easily dissolves. The dissolved Mn rapidly deposits onto the SEI film of the negative electrode, damaging the SEI film and accelerating the capacity decay of the secondary battery. Furthermore, at higher voltages (greater than or equal to 4V), spinel-structured manganese-rich materials catalyze the oxidative decomposition of the electrolyte, also accelerating the capacity decay. Therefore, it is necessary to coat the surface of manganese-containing positive electrode active materials such as spinel-structured manganese-rich materials to prevent their interaction with the electrolyte. However, due to the low surface energy of spinel-structured manganese-rich materials, it is difficult to form a uniform and dense coating on their surface, resulting in a significant amount of Mn still depositing onto the negative electrode, leading to severe capacity decay in the secondary battery.
[0054] Therefore, this application provides a secondary battery comprising a positive electrode, a negative electrode, and an electrolyte. The positive electrode comprises a positive active material, which includes a core and a surface layer. The core comprises a first spinel-type material containing manganese, wherein the molar percentage of manganese in the first spinel-type material is R1, where R1 is greater than or equal to 0.1 and less than or equal to 0.4. The surface layer covers or adheres to the outer surface of the core and comprises a second spinel-type material, wherein the molar percentage of manganese in the second spinel-type material is R2, where R2 is greater than or equal to 0 and less than R1.
[0055] In this embodiment, the first spinel material contains manganese. A second spinel material is coated or attached to the surface of the first spinel material. The second spinel material has the same crystal form as the first spinel material, and their surface tensions are similar. This allows the second spinel material to coat or attach to the surface of the first spinel material more uniformly and densely. The molar percentage R2 of manganese in the second spinel material is less than that in the first spinel material. The molar percentage of manganese in the material, R1, indicates that the stability of the second spinel material is greater than that of the first spinel material. This allows the second spinel material to protect the first spinel material, reducing the probability of the first spinel material coming into contact with the electrolyte, reducing the probability of manganese from the first spinel material dissolving into the electrolyte, reducing the amount of manganese deposited on the SEI film surface of the negative electrode, reducing damage to the SEI film, improving the capacity decay of the secondary battery, and enhancing the storage performance of the secondary battery. In the embodiments of this application, R1 can be 0.1, 0.13, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.33, 0.34, or a range of the above two values, such as 0.1≤R1<0.2, 0.2≤R1<0.3, 0.3≤R1≤0.4, etc.
[0056] In this embodiment, the surface layer is coated or attached to the outer surface of the core. Coating involves forming a shell or membrane on the core surface through physical, chemical, or biological means, thus encapsulating the core. Attachment refers to fixing or binding micro / nano particles to the core surface through physical or chemical processes, with numerous micro / nano particles forming the surface layer.
[0057] In this embodiment of the application, the molar percentage of manganese in the first spinel-type material refers to the molar percentage of manganese based on the total molar percentage of all elements in the first spinel-type material. Similarly, the molar percentage of manganese in the second spinel-type material refers to the molar percentage of manganese based on the total molar percentage of all elements in the second spinel-type material.
[0058] In some embodiments, the sum of the molar percentages of nickel and manganese in the first spinel material is R3, where R3 is greater than or equal to R1; the sum of the molar percentages of nickel and manganese in the second spinel material is R4, where R4 is greater than or equal to R2 and less than R3. In this embodiment, during the charging and discharging process of the secondary battery, when fully charged, the nickel in the positive electrode active material exhibits a +4 oxidation state, resulting in strong oxidizing properties and a tendency to undergo side reactions with the electrolyte. In this embodiment, by controlling the sum of the molar percentages of nickel and manganese in the second spinel material to be less than that of the first spinel material (i.e., R4 < R3), the second spinel material exhibits stronger stability and lower oxidizing properties during full charge compared to the first spinel material. This protects the first spinel material, reduces the probability of side reactions between the positive electrode active material and the electrolyte, improves the capacity retention rate of the secondary battery, and enhances its storage performance.
[0059] In the embodiments of this application, the molar percentages of manganese and nickel in the first spinel-type material and the second spinel-type material can be determined by one or more of the following methods: X-ray diffraction (XRD) to detect the phase, inductively coupled plasma (ICP) to test the elemental content, X-ray photoelectron spectroscopy (XPS) to test the elemental and valence state distribution, energy dispersive spectroscopy (EDS) to analyze the elemental distribution, and transmission electron microscopy (TEM) to analyze the lattice fringes, or by combination and calculation.
[0060] In some embodiments, the first spinel-type material comprises Li x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1The material has the following properties: 0.9≤x1≤1.2, 0≤y1≤0.3, 0.9≤x1+y1≤1.2, 1≤r1≤2, 0≤d1≤0.6, -0.1≤k1≤0.5, 0≤δ1≤0.5; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Me includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Cr, B, Al, Ga, In, Sc, Ti, V, Mn, Fe, Co, Y, Zr, Nb, Mo, Pb, Ta, W, lanthanides, C, Si, Ge, Sn, Pb, Sb, Bi, Te, P, and S; G includes one or more of F, Cl, Br, and I. In the embodiments of this application, the first spinel-type material comprising the above chemical formula has a high energy density. In this embodiment of the application, r1 can be 1, 1.2, 1.4, 1.5, 1.7, 2, etc., or a range of any two of the above values, such as 1≤r1≤1.4, 1.4≤r1≤1.7, 1.7≤r1≤2, etc. In this embodiment of the application, the lanthanide elements include La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), Lu (lutetium), etc.
[0061] In the embodiments of this application, Li x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1 The spinel structure features a close-packed cubic arrangement of O and G ions, with Li and A ions filling the interstitial positions of the oxygen tetrahedra, and Me, Ni, and Mn ions filling the interstitial positions of the oxygen octahedrons. It should be noted that elements such as Be, Mg, Ca, Sr, Ba, Ni, Cu, Zn, Pt, Ag, and Cr may theoretically occupy either interstitial or octahedral positions within the crystal structure, depending primarily on the type and proportion of elements they are paired with. For example, LiMg... 0.1 Mn 1.9 O4, the Li sites are full, and the Mn sites are vacant, so Mg is at the Mn site, that is, Mg is Me, located in the interstitial position of the oxygen octahedron in the crystal structure. For example: Li 0.9 Mg 0.1 In Mn2O4, the Mn sites are full and the Li sites are vacant, so Mg is in the Li sites, that is, Mg is A, located in the interstitial position of the oxygen tetrahedron in the crystal structure.
[0062] In some embodiments, the second spinel-type material includes materials with the chemical formula Li. x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The materials are 0≤x²≤2, 0≤y²≤2, 0.9≤x²+y²≤2, 0≤r²<2, 0≤d²≤0.6, 0≤a²≤2, 0≤b²≤2, 0≤r²<2, -0.1≤k²≤0.5, 0≤δ²≤2; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Ma includes one or more of Cr, Sc, V, Fe, Co, and Ni; Mb includes one or more of B, Al, Ti, Zr, Nb, Mo, Ta, W, Ce, Si, Te, and P; Mc includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Ga, In, Y, Pb, lanthanides, C, Ge, Sn, Pb, Sb, Bi, and S; G includes one or more of F, Cl, Br, and I. In this embodiment, the second spinel-type material includes materials with the aforementioned chemical formula, resulting in higher structural stability, lower oxidation resistance, and higher acid resistance. This allows the second spinel-type material to protect the first spinel-type material. In this embodiment, the element contained in Mb can stabilize the oxygen element in the spinel structure, improving the stability of the second spinel-type material. In this embodiment, r2 can be 0, 0.2, 0.4, 0.5, 0.7, 1, 1.3, 1.4, 1.5, 1.8, 2, etc., or a range of any two of the above values, such as 0≤r1≤0.7, 0.7≤r1≤1.4, 1.4≤r1≤2, etc. Lanthanide elements include La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), and Lu (lutetium).
[0063] In the embodiments of this application, Li x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2In the spinel structure, O and G ions are closely packed in a cubical pattern, while Li and A ions fill the interstitial positions of the oxygen tetrahedra, and Mn, Ni, Ma, Mb, and Mc ions fill the interstitial positions of the oxygen octahedrons. Theoretically, elements such as Be, Mg, Ca, Sr, Ba, Ni, Cu, Zn, Pt, Ag, and Cr may be located in either the interstitial or octahedral positions, depending primarily on the type and proportion of elements they are paired with.
[0064] In the embodiments of this application, the chemical formulas of the first spinel-type material and the second spinel-type material can be determined by one or a combination of several of the following methods: X-ray diffraction (XRD) to detect phases, inductively coupled plasma (ICP) to test elemental content, X-ray photoelectron spectroscopy (XPS) to test elemental and valence state distribution, energy dispersive spectroscopy (EDS) to analyze elemental distribution, and transmission electron microscopy (TEM) to analyze lattice fringes.
[0065] In some implementations, 0 ≤ r2 < 1. In the embodiments of this application, r2 is controlled within the above range, i.e., Li x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The subscript of manganese in the second spinel material is less than 1 and greater than or equal to 0, resulting in a lower manganese content. This reduces the probability of manganese dissolution in the second spinel material, thereby decreasing its catalytic activity and the probability of it catalyzing electrolyte reactions, ultimately improving the capacity retention of the secondary battery. In this embodiment, r2 can be 0, 0.2, 0.4, 0.5, 0.7, 1, or any range of two of these values, such as 0≤r1≤0.4, 0.4≤r1≤0.7, 0.7≤r1≤1, etc.
[0066] In some embodiments, 0 ≤ a2 ≤ 1. In the embodiments of this application, Ma contains elements with high reactivity, and Li is controlled... x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2In the case of Ma, the subscript a2 is less than or equal to 1 and greater than or equal to 0, resulting in a lower content of highly active elements. This helps to reduce the catalytic activity of the second spinel-type material, decrease the probability of the second spinel-type material catalyzing the electrolyte reaction, and improve the capacity retention rate of the secondary battery. In the embodiments of this application, a2 can be 0, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 1, etc., or a range of any two of the above values, such as 0≤a2≤0.3, 0.3≤a2≤0.6, 0.6≤a2≤1, etc.
[0067] In some embodiments, 0 < x2 ≤ 1.2. In the embodiments of this application, x2 is within the above range, which allows the second spinel-type material to contain lithium ions as active ions, enabling the active ions to migrate rapidly on the surface and exhibiting better kinetic performance, thus facilitating the rapid charge-discharge performance of the secondary battery. In the embodiments of this application, x2 can be 0.01, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 1, 1.2, etc., or a range of any two of the above values, such as 0 < x2 ≤ 0.01, 0.01 ≤ x2 ≤ 0.2, 0.2 ≤ x2 ≤ 0.7, 0.7 ≤ x2 ≤ 1.2, etc.
[0068] In some embodiments, 1 ≤ b2 ≤ 2. In the embodiments of this application, by controlling the subscript b2 of Mb within the above range, the subscript of Mb is made larger, resulting in a higher Mb element content. This stabilizes the oxygen element in the spinel structure, which is beneficial to improving the structural stability of the second spinel-type material, improving the stability of the positive electrode active material, reducing the probability of side reactions between the positive electrode active material and the electrolyte, and improving the capacity retention rate of the secondary battery. In the embodiments of this application, b2 can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 2, etc., or a range of any two of the above values, such as 1 < b2 ≤ 1.2, 1.2 ≤ b2 ≤ 1.6, 1.6 ≤ b2 ≤ 2, etc.
[0069] In some embodiments, Mb includes one or more of Zr, Nb, Mo, Ta, Te, and P. In the embodiments of this application, Mb includes one or more of the above elements, which can better stabilize the oxygen element in the second spinel-type material, improve the stability of the second spinel-type material, improve the stability of the positive electrode active material, and help improve the capacity retention rate of the secondary battery.
[0070] In some embodiments, the first spinel-type material includes one or more of lithium manganese oxide, lithium nickel manganese oxide, lithium nickel iron manganese oxide, lithium nickel iron aluminum niobium manganese oxide, and lithium nickel copper iron aluminum niobium manganese oxide. The second spinel-type material includes one or more of lithium nickel manganese oxide, lithium iron manganese oxide, lithium iron aluminum niobium titanium manganese oxide, lithium iron zirconium antimony manganese oxide, lithium aluminum niobium titanium manganese oxide, lithium cobalt aluminum niobium titanium manganese oxide, lithium iron aluminum niobium titanium manganese oxide, lithium magnesium aluminum niobium titanium manganese oxide, lithium copper titanium manganese oxide, magnesium iron manganese aluminum titanium oxide, lithium magnesium aluminum antimony oxide, and magnesium aluminum oxide. In the embodiments of this application, the first spinel-type material and the second spinel-type material respectively include the above-mentioned materials. The second spinel-type material coats or adheres to the surface of the first spinel-type material, resulting in lower catalytic activity and lower oxidizing power of the positive electrode active material, acid resistance, stronger stability of the positive electrode active material, and better capacity retention of the secondary battery. For example, the first type of spinel material can be lithium manganese oxide, and the second type of spinel material can be lithium nickel manganese oxide. The content of manganese in the second type of spinel material (the percentage of molar number of elements) is less than the content of manganese in the first type of spinel material. The lithium in the second type of spinel can enter the manganese site, so that the total content of nickel and manganese in the second type of spinel is less than the total content of manganese in the first type of spinel.
[0071] In some embodiments, the surface layer includes a non-spinel material, which includes one or more of inorganic substances with melting points below 1000°C, glucose, sucrose, fructose, amorphous carbon, and organic polymers. In embodiments of this application, the surface layer further includes a non-spinel material. Mixing the non-spinel material with a second spinel material can disperse the second spinel material, resulting in a more uniform dispersion and improving the density of the coating or adhesion of the surface layer to the surface of the first spinel material.
[0072] In some embodiments, the inorganic material with a melting point below 1000°C includes one or more of lithium phosphate, lithium borate, boric acid, vanadium pentoxide, and boron oxide. In the embodiments of this application, lithium phosphate can suppress the dissolution of manganese ions in the first spinel-type material and improve lithium-ion conductivity; coating or attaching lithium phosphate can improve the density of the surface layer. Boric acid and lithium borate can suppress the dissolution of manganese ions; lithium borate can improve the compatibility between the electrolyte and the positive electrode active material, reduce side reactions between the positive electrode active material and the electrolyte, and improve the capacity retention rate of the secondary battery. Vanadium pentoxide can improve electronic conductivity, reduce resistance, participate in the formation of the SEI film, and improve the density of the surface layer coated or attached to the first spinel-type material. Boron oxide can enhance the structural stability of the positive electrode active material and improve the capacity retention rate of the secondary battery.
[0073] In some embodiments, the organic polymer includes one or more of polyacrylic acid, lithium polyacrylate, cyclohexanehexaphosphate, and phenolic resin. In this application embodiment, the organic polymer can disperse the second spinel-type material, improving the density of the coating or attachment on the surface of the first spinel-type material. Specifically, polyacrylic acid can reduce the erosion of the first spinel-type material by the electrolyte and reduce the dissolution of manganese ions from the first spinel-type material. Lithium polyacrylate can act as a lithium-ion conductor, mixing with the second spinel-type material to coat or attach to the surface of the first spinel-type material, enhancing the ion contact between the positive electrode active material and the electrolyte, and participating in the formation of the SEI film, reducing side reactions and improving electrochemical performance. The multiple phosphate groups in cyclohexanehexaphosphate can chelate with metallic manganese ions, reducing the reach of manganese ions from the positive electrode active material to the SEI film of the negative electrode, reducing the damage of the SEI film layer by manganese ions, and improving the capacity retention rate of the secondary battery. Phenolic resin is mixed with a second spinel-type material to coat or attach to the outer surface of the first spinel-type material, which can form a dense surface layer, reduce the probability of direct contact between the first spinel-type material and the electrolyte, and improve the stability of the positive electrode active material.
[0074] In some embodiments, the mass ratio of the non-spinel material to the second spinel material is greater than or equal to 0 and less than or equal to 2. In this application embodiment, by controlling the mass ratio of the non-spinel material to the second spinel material within the above range, the non-spinel material can disperse the second spinel material, improving the uniformity of the second spinel material in the surface layer and increasing the density of the coating or adhesion on the surface of the first spinel material. The coating or adhesion of the second spinel material to the surface of the first spinel material can protect the first spinel material. Simultaneously, the second spinel material can provide ion transport channels, facilitating the transport of active ions and improving the capacity retention rate of the secondary battery. In this embodiment of the application, the mass ratio of the non-spinel material to the second spinel material can be 0, 0.4, 0.5, 0.8, 1, 1.2, 1.5, 1.8, 2, etc., or a range of any two of the above values, such as 0 to 0.8, 0.8 to 1.2, 1.2 to 2, etc.
[0075] In some embodiments, the mass ratio of the non-spinel material to the second spinel material is greater than or equal to 0.1 and less than or equal to 1. In the embodiments of this application, the mass ratio of the non-spinel material to the second spinel material is within the above range, resulting in a better proportion of the second spinel material in the surface layer, which is beneficial for protecting the first spinel material and improving the capacity retention rate of the secondary battery. In the embodiments of this application, the mass ratio of the non-spinel material to the second spinel material can be 0.1, 0.4, 0.5, 0.8, 1, etc., or a range of any two of the above values, such as 0.1–0.4, 0.4–0.8, 0.8–1, etc.
[0076] In some embodiments, the surface layer accounts for 0.01% to 30% of the total mass of the positive electrode active material. In this embodiment, by controlling the surface layer's mass percentage within the above range, a uniform coating or adhesion layer can be formed on the surface of the first spinel-type material, while simultaneously giving the positive electrode active material better electrochemical performance. In this embodiment, the surface layer's mass percentage, based on the total mass of the positive electrode active material, can be 0.01%, 0.05%, 0.08%, 0.1%, 0.8%, 1%, 3%, 5%, 10%, 15%, 18%, 20%, 26%, 30%, etc., or a range of any two of the above values, such as 0.01% to 0.1%, 0.1% to 10%, 10% to 18%, 18% to 30%, etc.
[0077] In some embodiments, the volume average particle size D of the positive electrode active material V 50 represents the particle size range of 1 μm to 50 μm. In the embodiments of this application, the volume average particle size D of the positive electrode active material is... V Within the aforementioned range, the positive electrode sheet possesses high compaction density and mechanical strength, which is beneficial for achieving high energy density in the secondary battery. In the embodiments of this application, the volume average particle size DV50 of the positive electrode active material is 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 26 μm, 30 μm, 36 μm, 40 μm, 45 μm, 48 μm, 50 μm, etc., or a range consisting of any two of the above values, such as 1 μm to 10 μm, 10 μm to 26 μm, 26 μm to 50 μm, etc.
[0078] In this embodiment of the application, the volume average particle size D V 50 refers to the particle size value corresponding to a cumulative volume percentage of 50% in the particle's volume distribution. Volume average particle size D V 50 is common knowledge in the field, has a common meaning in the field, and can be measured by methods and instruments in the field.
[0079] In some embodiments, the volume average particle size D of the positive electrode active material V 50 represents a particle size ranging from 2 μm to 20 μm. In the embodiments of this application, the volume average particle size D of the positive electrode active material is... V Within the aforementioned range, the positive electrode sheet possesses high compaction density and mechanical strength, which is beneficial for achieving higher energy density in the secondary battery. In the embodiments of this application, the volume average particle size Dv50 of the positive electrode active material is 2μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm, 20μm, etc., or a range consisting of any two of the above values, such as 2μm~8μm, 8μm~13μm, 13μm~20μm, etc.
[0080] The second aspect of this application includes a positive electrode active material, comprising a core and a surface layer. The core comprises a first spinel-type material containing manganese, wherein the molar percentage of manganese in the first spinel-type material is R1, and R1 is greater than or equal to 0.1 and less than or equal to 0.4. The surface layer covers or adheres to the outer surface of the core, and the surface layer comprises a second spinel-type material, wherein the molar percentage of manganese in the second spinel-type material is R2, and R2 is greater than or equal to 0 and less than R1.
[0081] The positive electrode active material in this application includes a core containing a first type of spinel material and a surface layer containing a second type of spinel material. The second type of spinel material has the same crystal form and similar surface tension as the first type of spinel material. By coating or attaching the second type of spinel material to the outer surface of the first type of spinel material, the second type of spinel material can be uniformly and densely coated or attached to the surface of the first type of spinel material. The molar ratio R2 of manganese element in the second type of spinel material is less than the molar ratio R1 of manganese element in the first type of spinel material. The stability of the second type of spinel material is greater than that of the first type of spinel material. This allows the second type of spinel material to protect the first type of spinel material, reduce the amount of manganese dissolved from the first type of spinel material, and improve the stability of the positive electrode active material.
[0082] In some embodiments, the sum of the molar percentages of nickel and manganese in the first spinel material is R3, where R3 is greater than or equal to R1; the sum of the molar percentages of nickel and manganese in the second spinel material is R4, where R4 is greater than or equal to R2 and less than R3. In the embodiments of this application, by controlling the sum of the molar percentages of nickel and manganese in the second spinel material to be less than that in the first spinel material (i.e., R4 < R3), the second spinel material exhibits stronger stability and lower oxidizability than the first spinel material when fully charged in a secondary battery. This protects the first spinel material, reduces the probability of side reactions between the positive electrode active material and the electrolyte, and improves the capacity retention rate of the positive electrode active material.
[0083] In some embodiments, the first spinel-type material comprises Li x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1 The material has the following chemical formulas: 0.9≤x1≤1.2, 0≤y1≤0.3, 0.9≤x1+y1≤1.2, 1≤r1≤2, 0≤d1≤0.6, -0.1≤k1≤0.5, 0≤δ1≤0.5; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Me includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Cr, B, Al, Ga, In, Sc, Ti, V, Mn, Fe, Co, Y, Zr, Nb, Mo, Pb, Ta, W, lanthanides, C, Si, Ge, Sn, Pb, Sb, Bi, Te, P, and S; G includes one or more of F, Cl, Br, and I. In the embodiments of this application, the first spinel-type material includes the material with the above chemical formula, which makes the positive electrode active material have a high energy density. In this embodiment of the application, r1 can be 1, 1.2, 1.4, 1.5, 1.7, 2, etc., or a range of any two of the above values, such as 1≤r1≤1.4, 1.4≤r1≤1.7, 1.7≤r1≤2, etc. In this embodiment of the application, the lanthanide elements include La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), Lu (lutetium), etc.
[0084] In some embodiments, the second spinel-type material includes materials with the chemical formula Li.x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The materials are 0≤x²≤2, 0≤y²≤2, 0.9≤x²+y²≤2, 0≤r²<2, 0≤d²<0.6, 0≤a²≤2, 0≤b²≤2, 0≤r²<2, -0.1≤k²≤0.5, 0≤δ²≤2; Ma includes one or more of Cr, Sc, V, Fe, Co, and Ni; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Mb includes one or more of B, Al, Ti, Zr, Nb, Mo, Ta, W, Ce, Si, Te, and P; Mc includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Ga, In, Y, Pb, lanthanides, C, Ge, Sn, Pb, Sb, Bi, and S; G includes one or more of F, Cl, Br, and I. In this embodiment, the second spinel-type material includes materials with the aforementioned chemical formula, resulting in higher structural stability, lower oxidation resistance, and higher acid resistance. This allows the second spinel-type material to protect the first spinel-type material. In this embodiment, the element contained in Mb can stabilize the oxygen element in the spinel structure, improving the stability of the second spinel-type material. In this embodiment, r2 can be 0, 0.2, 0.4, 0.5, 0.7, 1, 1.3, 1.4, 1.5, 1.8, 2, etc., or a range of any two of the above values, such as 0≤r1≤0.7, 0.7≤r1≤1.4, 1.4≤r1≤2, etc. Lanthanide elements include La (lanthanum), Ce (cerium), Pr (praseodymium), Nd (neodymium), Pm (promethium), Sm (samarium), Eu (europium), Gd (gadolinium), Tb (terbium), Dy (dysprosium), Ho (holmium), Er (erbium), Tm (thulium), Yb (ytterbium), and Lu (lutetium).
[0085] In some embodiments, the surface layer includes a non-spinel material, which includes one or more of inorganic substances with melting points below 1000°C, glucose, sucrose, fructose, amorphous carbon, and organic polymers. In embodiments of this application, the surface layer further includes a non-spinel material. Mixing the non-spinel material with a second spinel material can disperse the second spinel material, resulting in a more uniform dispersion and improving the density of the coating or adhesion of the surface layer to the surface of the first spinel material.
[0086] A third aspect of this application includes an electrical device comprising a secondary battery as described in the first aspect, and / or a positive electrode active material as described in the second aspect. The electrical device in the embodiments of this application has the secondary battery of the first aspect and / or the positive electrode active material of the second aspect, possessing the same advantages as the secondary battery of the first aspect and / or the same advantages as the positive electrode active material of the second aspect.
[0087] For ease of explanation, the following embodiments will be described using a vehicle 1000 as an example of an electrical device according to an embodiment of this application.
[0088] Please refer to Figure 1 , Figure 1 This is a schematic diagram of the structure of a vehicle 1000 provided in some embodiments of this application. The vehicle 1000 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A secondary battery 100 is installed inside the vehicle 1000, and the secondary battery 100 can be located at the bottom, front, or rear of the vehicle 1000. The secondary battery 100 can be used to power the vehicle 1000; for example, the secondary battery 100 can serve as the operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the secondary battery 100 to supply power to the motor 300, for example, to meet the power needs of the vehicle 1000 during startup, navigation, and driving.
[0089] In some embodiments of this application, the secondary battery 100 can not only serve as the operating power source for the vehicle 1000, but also as the driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.
[0090] Please refer to Figure 2 , Figure 2This is an exploded structural diagram of a secondary battery 100 provided in some embodiments of this application. The secondary battery 100 includes a housing 10 and a battery cell 20, with the battery cell 20 housed within the housing 10. The housing 10 provides a space for the battery cell 20 and can have various structures. In some embodiments, the housing 10 may include a first portion 11 and a second portion 12, which overlap each other, jointly defining a space for accommodating the battery cell 20. The second portion 12 may be a hollow structure with one open end, and the first portion 11 may be a plate-like structure, covering the open side of the second portion 12 so that the first portion 11 and the second portion 12 jointly define the space; alternatively, the first portion 11 and the second portion 12 may both be hollow structures with one open side, with the open side of the first portion 11 covering the open side of the second portion 12. Of course, the housing 10 formed by the first portion 11 and the second portion 12 can have various shapes, such as a cylinder, a cuboid, etc.
[0091] In the secondary battery 100, there can be multiple battery cells 20, which can be connected in series, parallel, or in a mixed manner. A mixed connection means that multiple battery cells 20 are connected in both series and parallel. Multiple battery cells 20 can be directly connected in series, parallel, or in a mixed manner, and then the whole assembly of multiple battery cells 20 is housed in the housing 10. Of course, the secondary battery 100 can also be composed of multiple battery cells 20 first connected in series, parallel, or in a mixed manner to form a battery module, and then multiple battery modules are connected in series, parallel, or in a mixed manner to form a whole, which is also housed in the housing 10.
[0092] The battery cell 20 can be a lithium-sulfur battery, a sodium-ion battery, or a magnesium-ion battery, but is not limited to these. The battery cell 20 can be cylindrical, flat, cuboid, or other shapes.
[0093] Please refer to Figure 3 , Figure 3 This is an exploded structural diagram of a battery cell 20 provided in some embodiments of this application. The battery cell 20 refers to the smallest unit constituting the secondary battery 100. For example... Figure 3 The battery cell 20 includes an end cap 21, a housing 22, a cell assembly 23, and other functional components.
[0094] End cap 21 refers to a component that covers the opening of housing 22 to isolate the internal environment of battery cell 20 from the external environment. The shape of end cap 21 can be adapted to the shape of housing 22 to fit it. Optionally, end cap 21 can be made of a material with certain hardness and strength (such as aluminum alloy), so that end cap 21 is not easily deformed under pressure and impact, allowing battery cell 20 to have higher structural strength and improved safety performance. Functional components such as electrode terminals 21a can be provided on end cap 21. Electrode terminals 21a can be used for electrical connection with cell assembly 23 to output or input electrical energy to battery cell 20. In some embodiments, end cap 21 can also be provided with a pressure relief mechanism for releasing internal pressure when the internal pressure or temperature of battery cell 20 reaches a threshold. The material of end cap 21 can also be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and this application embodiment does not impose special limitations on this. In some embodiments, an insulating element may be provided on the inner side of the end cap 21. The insulating element can be used to isolate the electrical connection components within the housing 22 from the end cap 21 to reduce the risk of short circuits. For example, the insulating element may be made of plastic, rubber, etc.
[0095] The housing 22 is a component used to cooperate with the end cap 21 to form the internal environment of the battery cell 20. This internal environment can accommodate the cell assembly 23, electrolyte, and other components. The housing 22 and the end cap 21 can be independent components. An opening can be provided on the housing 22, and the end cap 21 can be used to close the opening to form the internal environment of the battery cell 20. Alternatively, the end cap 21 and the housing 22 can be integrated. Specifically, the end cap 21 and the housing 22 can form a common connecting surface before other components are inserted into the housing. When it is necessary to encapsulate the interior of the housing 22, the end cap 21 closes the housing 22. The housing 22 can be of various shapes and sizes, such as cuboid, cylindrical, hexagonal prism, etc. Specifically, the shape of the housing 22 can be determined according to the specific shape and size of the cell assembly 23. The material of the housing 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc. This application embodiment does not impose any special limitations on this.
[0096] The cell assembly 23 is the component in the battery cell 20 where the electrochemical reaction occurs. The casing 22 may contain one or more cell assemblies 23. The cell assembly 23 is mainly formed by winding or stacking positive and negative electrode plates, and typically a separator is provided between the positive and negative electrode plates. The portions of the positive and negative electrode plates containing active material constitute the main body of the cell assembly, while the portions of the positive and negative electrode plates without active material each constitute a tab 23a. The positive and negative tabs may be located together at one end of the main body or separately at both ends of the main body. During the charging and discharging process of the secondary battery 100, the positive and negative active materials react with the electrolyte, and the tabs 23a connect to the electrode terminals to form a current loop.
[0097] [Positive electrode plate]
[0098] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one surface of the positive current collector.
[0099] As an example, the positive current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode film layer is disposed on either or both of the two opposite surfaces of the positive current collector.
[0100] In some embodiments, the positive current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0101] In some embodiments, the positive electrode film layer includes a positive electrode active material, and the layer may optionally include a binder. The binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0102] In some embodiments, the positive electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0103] In some embodiments, the positive electrode sheet can be prepared by dispersing the above-mentioned components for preparing the positive electrode sheet, such as positive active material, conductive agent, second binder and any other components, in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the positive electrode current collector, and then obtaining the positive electrode sheet after drying, cold pressing and other processes.
[0104] [Negative electrode plate]
[0105] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material.
[0106] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on either or both of the two opposite surfaces of the negative electrode current collector.
[0107] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0108] In some embodiments, the negative electrode active material may be a negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. Silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0109] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0110] In some embodiments, the negative electrode film may optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0111] In some embodiments, the negative electrode film may optionally include other additives, such as thickeners (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0112] In some embodiments, the negative electrode sheet can be prepared by dispersing the components used to prepare the negative electrode sheet, such as the negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0113] [Isolation membrane]
[0114] This application does not impose any particular restrictions on the type of separator membrane; any known porous separator membrane with good chemical and mechanical stability can be selected.
[0115] In some embodiments, the material of the separator can be selected from at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular limitation. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0116] [Electrolytes]
[0117] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0118] In some embodiments, the electrolyte is an electrolyte solution. The electrolyte solution includes an electrolyte salt and a solvent.
[0119] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0120] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butyl carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.
[0121] In some embodiments, the electrolyte may optionally include additives. For example, additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc.
[0122] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into a battery cell assembly using a winding or stacking process.
[0123] In some implementations, the housing can be a rigid housing, such as a hard plastic housing, an aluminum housing, a steel housing, etc.
[0124] This application does not impose any particular restrictions on the shape of the battery cell; it can be cylindrical, square, or any other arbitrary shape.
[0125] The beneficial effects of this application are further illustrated below with reference to the embodiments.
[0126] To make the technical problems, technical solutions, and beneficial effects solved by the embodiments of this application clearer, the following will provide a more detailed description in conjunction with the embodiments and accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit this application or its applications. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. Here, "nanoscale" refers to particles with a diameter between 1 nm and 900 nm.
[0127] I. Preparation of Positive Electrode and Secondary Battery
[0128] Example 1:
[0129] 1) Production of the positive electrode sheet:
[0130] 1.1) Preparation of positive electrode active material:
[0131] 1.11) Preparation of the first spinel-type material:
[0132] Lithium carbonate (Li₂CO₃), nickel oxide (NiO), and manganese dioxide (MnO₂) were mixed in an elemental ratio of Li:Ni:Mn of 1.0:0.5:1.5 and kept at 950℃ for 20 hours to obtain the first spinel-type material, Li. 1.0 Ni 0.5 Mn 1.5 O 3.86 In the embodiments of this application, the first spinel-type material Li 1.0 Ni 0.5 Mn 1.5 O 3.86 It has a spinel structure.
[0133] 1.12) Preparation of the second type of spinel material:
[0134] The raw materials lithium carbonate (Li₂CO₃), ferric oxide (Fe₂O₃), aluminum oxide (Al₂O₃), niobium pentoxide (Nb₂O₅), titanium dioxide (TiO₂), and manganese dioxide (MnO₂) were mixed in an elemental molar ratio of Li:Fe:0.5:0.3:0.2:0.5:0.5. The mixture was then heated at 1000℃ for 20 hours and crushed to obtain a second nanoscale spinel-type material, Li. 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O 4.00 In the embodiments of this application, the second spinel-type material Li 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O 4.00 It has a spinel structure.
[0135] 1.13) Preparation of positive electrode active material:
[0136] The first spinel-type material Li 1.0 Ni 0.5 Mn 1.5 O 3.86 The positive electrode active material is prepared by uniformly mixing the surface material with the surface material at a mass ratio of 97:3 and heating to 800℃ for 10 hours in air atmosphere. The surface material includes a compound with the chemical formula Li. 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O4 materials, Li1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O4 has a spinel structure. In the embodiments of this application, the positive electrode active material includes a core and a surface layer, and the core is Li. 1.0 Ni 0.5 Mn 1.5 O 3.86 The surface layer is Li 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O4, with a surface coating on the outer surface of the core, has a volume-average particle size D of the positive electrode active material. V 50 is 8μm.
[0137] 1.2) Production of the positive electrode sheet:
[0138] The positive electrode active material was mixed with conductive carbon black (Super P) and PVDF at a weight ratio of 96:2.5:1.5, and an appropriate amount of solvent N-methylpyrrolidone (NMP) was added. The mixture was stirred until homogeneous to obtain a positive electrode slurry. The positive electrode slurry was coated onto aluminum foil, dried, and then cold-pressed to obtain a positive electrode sheet. The active material loading on the positive electrode sheet was 0.016 g / cm³. 2 .
[0139] 2) Fabrication of the negative electrode sheet:
[0140] Artificial graphite (anode active material), carbon black (Super P) (conductive agent), styrene-butadiene rubber (binder), and sodium carboxymethyl cellulose (thickener) were mixed thoroughly in an appropriate amount of deionized water at a mass ratio of 96:1:1:2 to form a uniform negative electrode slurry. This slurry was then uniformly coated onto the surface of a copper foil current collector. After drying and cold pressing, a negative electrode active film was formed, resulting in the negative electrode sheet. The loading of the negative electrode active material on one side of the current collector was 0.007 g / cm³. 2 .
[0141] 3) Separating membrane:
[0142] A 12μm thick polypropylene film.
[0143] 4) Electrolyte:
[0144] Methyltrifluoroethyl carbonate (FEMC) and fluoroethylene carbonate (FEC) were mixed at a volume ratio of 7:3. LiPF6 was then dissolved in the above solution to obtain an electrolyte in which the molar concentration of LiPF6 was 1 mol / L.
[0145] 5) Assembly:
[0146] The positive electrode, separator, and negative electrode obtained above are arranged in sequence, with the separator positioned between the positive and negative electrodes to provide isolation. The mixture is then shaped and packaged in an aluminum-plastic bag. Electrolyte is injected, and after encapsulation, capacity is formed to obtain a secondary battery (soft-pack battery).
[0147] Examples 2 to 13
[0148] The difference between Examples 2 to 13 and Example 1 lies in 1.12) the preparation of the second spinel-type material and the chemical formula of the second spinel-type material. Other preparation methods are the same as in Example 1, and specific parameters are detailed in Tables 1 and 2. The proportions of raw materials added are based on the proportions of each element in the chemical composition in Table 1.
[0149] In Example 2, the raw materials are lithium carbonate (Li2CO3), ferric oxide (Fe2O3), aluminum oxide (Al2O3), niobium pentoxide (Nb2O5), and titanium dioxide (TiO2), and the raw materials are mixed in a molar ratio of Li, Fe, Al, Nb, and Ti of 1.02:0.5:0.3:0.2:1.0.
[0150] In Examples 3 to 5, the amount of raw materials added satisfies the molar ratio of elements Li, Fe, Al, Nb, Ti, and Mn as 1.02:0.5:0.2:0.1:0.2:1.0, 1.02:0.3:0.2:0.1:0.2:1.2, and 1.02:0.2:0.1:0.1:0.1:1.5.
[0151] In Example 6, the raw materials were lithium carbonate (Li2CO3), nickel oxide (NiO), ferric oxide (Fe2O3), aluminum oxide (Al2O3), titanium dioxide (TiO2), niobium pentoxide (Nb2O5), and manganese dioxide (MnO2). The amount of raw materials added met the requirement that the molar ratio of elements Li, Ni, Fe, Al, Nb, Ti, and Mn was 1.02:0.2:0.1:0.1:0.05:0.05:1.5.
[0152] In Example 7, the raw materials are lithium carbonate (Li2CO3), ferric oxide (Fe2O3), and manganese dioxide (MnO2), and the amount of raw materials added satisfies the elemental molar ratio of Li, Fe, and Mn as 1.02:0.5:1.5.
[0153] In Example 8, the raw materials were lithium carbonate (Li2CO3), ferric oxide (Fe2O3), zirconium oxide (ZrO2), tellurium oxide (TeO2), and manganese dioxide (MnO2), and the amount of raw materials added met the elemental molar ratio of Li, Fe, Zr, Te, and Mn of 1.02:0.5:0.5:0.5:0.5.
[0154] In Example 9, the raw materials are lithium carbonate (Li2CO3), aluminum oxide (Al2O3), niobium pentoxide (Nb2O5), titanium dioxide (TiO2), and manganese dioxide (MnO2), and the amount of raw materials added satisfies the elemental molar ratio of Li, Al, Nb, Ti, and Mn as 1.02:0.5:0.5:0.5:0.5.
[0155] In Example 10, the raw materials were lithium carbonate (Li2CO3), cobalt oxide (Co3O4), aluminum oxide (Al2O3), niobium pentoxide (Nb2O5), titanium dioxide (TiO2), and manganese dioxide (MnO2), and the amount of raw materials added met the requirement that the molar ratio of elements Li, Co, Al, Nb, Ti, and Mn was 1.02:0.5:0.3:0.2:0.5:0.5.
[0156] In Example 11, the amount of raw materials added satisfies the molar ratio of elements Li, Fe, Al, Nb, Ti, and Mn as 1.2:0.5:0.3:0.2:0.5:0.5.
[0157] In Example 12, the raw materials were lithium carbonate (Li2CO3), magnesium oxide (MgO), ferric oxide (Fe2O3), aluminum oxide (Al2O3), titanium dioxide (TiO2), and manganese dioxide (MnO2), and the amount of raw materials added met the elemental molar ratio of Li, Mg, Fe, Al, Ti, and Mn of 0.5:0.5:0.2:1.0:0.3:0.5.
[0158] In Example 13, the raw materials are magnesium oxide (MgO), ferric oxide (Fe2O3), aluminum oxide (Al2O3), and manganese dioxide (MnO2), and the amount of raw materials added satisfies the molar ratio of elements Mg, Fe, Al, and Mn as 1:0.5:1.0:0.5.
[0159] In Example 14, the raw materials are magnesium oxide (MgO) and aluminum oxide (Al2O3), and the amount of raw materials added satisfies the molar ratio of Mg to Al of 1:2.
[0160] Examples 15 to 18
[0161] The difference from Example 1 is that in 1.13) the first spinel-type material Li is used in the preparation of the positive electrode active material. 1.0 Ni 0.5 Mn1.5 O 3.86 The surface material is mixed with it in mass ratios of 99.9:0.1, 99:1, 90:10, 70:30, etc. Other manufacturing methods are the same as in Example 1, and specific parameters are detailed in Tables 1 and 2.
[0162] The difference between Examples 19 to 22 and Example 1 is that 1.11) the preparation of the first spinel-type material and the chemical formula of the first spinel-type material are the same as in Example 1. See Table 1 and Table 2 for details.
[0163] In Example 19, the amount of raw materials added satisfies the molar ratio of Li:Ni:Mn of 1.0:0.4:1.6.
[0164] In Example 20, the raw materials are lithium carbonate (Li2CO3), nickel oxide (NiO), ferric oxide (Fe2O3), and manganese dioxide (MnO2), and the amount of raw materials added satisfies the molar ratio of Li:Ni:Fe:Mn of 1.01:0.4:0.2:1.4.
[0165] In Example 21, the raw materials are lithium carbonate (Li2CO3), nickel oxide (NiO), ferric oxide (Fe2O3), aluminum oxide (Al2O3), niobium pentoxide (Nb2O5), and manganese dioxide (MnO2). The amount of raw materials added satisfies the molar ratio of elements Li:Ni:Fe:Al:Nb:Mn of 1.01:0.4:0.14:0.05:0.01:1.4.
[0166] In Example 22, the raw materials were lithium carbonate (Li2CO3), nickel oxide (NiO), copper oxide (CuO), ferric oxide (Fe2O3), aluminum oxide (Al2O3), niobium pentoxide (Nb2O5), and manganese dioxide (MnO2). The amount of raw materials added met the molar ratio of Li:Ni:Cu:Fe:Al:Nb:Mn of 1.01:0.4:0.04:0.10:0.05:0.01:1.4.
[0167] Example 23
[0168] The difference between Example 23 and Example 1 lies in 1.13) the preparation of the positive electrode active material. Specifically, 1.13) the preparation of the positive electrode active material:
[0169] The first spinel-type material Li 1.0 Ni 0.5 Mn 1.5 O 3.86 The positive electrode active material is prepared by uniformly mixing the surface material with the surface material at a mass ratio of 97:3 and heating to 800℃ for 10 hours in air atmosphere. The surface material includes a compound with the chemical formula Li.1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 The mass ratio of O4 to Li3PO4 is 2:1, and Li 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O4 has a spinel structure, and Li3PO4 has an olivine structure. In the embodiments of this application, the positive electrode active material includes a core and a surface layer, and the core is Li 1.0 Ni 0.5 Mn 1.5 O 3.86 The surface layer is Li 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O4 and Li3PO4 are coated on the outer surface of the core. The volume average particle size D of the positive electrode active material is... V 50 is 7.5μm.
[0170] Example 24
[0171] The difference between Example 24 and Example 1 lies in 1.13) the preparation of the positive electrode active material. Specifically, 1.13) the preparation of the positive electrode active material:
[0172] The first spinel-type material Li 1.0 Ni 0.5 Mn 1.5 O 3.86 The positive electrode active material is prepared by uniformly mixing the surface material with the surface material at a mass ratio of 97:3 and heating to 350℃ for 2 hours under a nitrogen atmosphere. The surface material includes Li 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 The mass ratio of O4 to asphalt is 2:1. Li 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O4 has a spinel structure. In the embodiments of this application, the positive electrode active material includes a core and a surface layer, and the core is Li. 1.0 Ni 0.5 Mn 1.5 O3.86 The surface layer is Li 1.02 Fe 0.5 Al 0.3 Nb 0.2 Ti 0.5 Mn 0.5 O4, asphalt, and amorphous carbon form a surface coating around the core; the amorphous carbon is formed by carbonizing asphalt at 350℃. The volume average particle size Dv50 of the positive electrode active material is 8.2 μm.
[0173] Comparative Example 1:
[0174] The difference between Comparative Example 1 and Example 1 lies in 1.13) the preparation of the positive electrode active material, specifically, 1.13) the preparation of the positive electrode active material:
[0175] The first spinel-type material Li 1.0 Ni 0.5 Mn 1.5 O 3.86 The positive electrode active material is prepared by heating to 800°C and holding at that temperature for 10 hours in air. In this embodiment, the positive electrode active material includes Li. 1.0 Ni 0.5 Mn 1.5 O 3.86 .
[0176] Comparative Example 2:
[0177] The difference between Comparative Example 1 and Example 1 is that (1.13) the surface material in the preparation of the positive electrode active material is corundum-type Al2O3, while the positive electrode active material in Comparative Example 2 includes a core and a surface layer, with the core being Li. 1.0 Ni 0.5 Mn 1.5 O 3.86 The surface layer is Al2O3, which covers the outer surface of the core.
[0178] II. Testing of cathode material parameters and electrochemical performance of secondary batteries
[0179] 1. Volume average particle size D V 50
[0180] Referring to GB / T 19077~2016, the volumetric particle size distribution curve of the material was obtained, and the particle size corresponding to the cumulative volume distribution percentage reaching 50% was taken as the volume average particle size D. V 50. The testing instrument was a Mastersirer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0181] 2. X-ray photoelectron spectroscopy (XPS) test
[0182] X-ray photoelectron spectroscopy (XSAM-800) was used to scan the negative electrode material samples. Al Kα radiation was used as the main excitation source. The binding energy shifts of the Mn 2p and Fe 2p spectra were corrected using the C1s standard binding energy of 284.5 eV.
[0183] 3. Scanning Electron Microscopy (SEM) Testing
[0184] The positive electrode active material was tested using a ZEISS Sigma 300 scanning electron microscope, and then the morphology of the sample was observed in accordance with the standard JY / T010-1996.
[0185] 4. Cross-sectional energy dispersive spectroscopy (EDS) test
[0186] The particle slices of the positive electrode active material are placed on the stage of a transmission electron microscope (TEM) and imaged under the electron beam generated by the electron gun to obtain the TEM microstructure of the sample.
[0187] After obtaining the TEM microstructure, the equipment is switched to X-ray energy dispersive spectroscopy (EDS) mode, and a full-field scan is performed within a specific field of view. When the electron beam interacts with the sample, the atoms in the sample are excited, emitting specific characteristic X-rays that are received by the EDS detector, allowing for analysis of the elemental composition of the corresponding region.
[0188] 5. Storage performance test
[0189] (1) At 25°C, the secondary battery (soft pack battery) is charged at a constant current of 0.33C to a voltage of 4.8V, and then charged at a constant voltage of 4.8V to a current of 0.05C. After standing for 5 minutes, the soft pack battery is discharged at a constant current of 0.33C to a voltage of 3.0V. This discharge capacity is the first discharge capacity C1 of the secondary battery.
[0190] (2) High-temperature full-charge storage performance test
[0191] At 25°C, the secondary battery (pouch cell) was charged at a constant current of 0.33C1 to a voltage of 4.8V, and then charged at a constant voltage of 4.8V to a current of 0.05C1. The pouch cell was then placed at 45°C for 100 days, removed, and allowed to cool to room temperature before being fully discharged. A full charge and discharge cycle was then performed at 25°C, and the discharge capacity value C was extracted. n C n / C1 represents the storage capacity retention rate over 100 days.
[0192] 6. Test of the mass percentage of manganese in the negative electrode sheet
[0193] At 25℃, the secondary battery (pouch battery) was charged at a constant current of 0.33C1 to a voltage of 4.8V, and then charged at a constant voltage of 4.8V to a current of 0.05C1. The pouch battery was then placed at 45℃ for 100 days, removed, and allowed to cool to room temperature before being fully discharged. The secondary battery was disassembled, the negative electrode was removed, and the negative electrode was soaked in DMC for 15 minutes. The negative electrode was then removed and dried. Approximately 2g of powder from the dried negative electrode was scraped off. Inductively coupled plasma (ICP) spectroscopy was used to determine the mass of manganese (Mn) in the negative electrode. The mass ratio of manganese in the negative electrode is the ratio of the mass of Mn in the negative electrode to the mass of the negative electrode active film layer.
[0194]
[0195]
[0196]
[0197]
[0198] like Figure 4a As shown, the base signal C1s of Example 1, Comparative Example 1, and Comparative Example 2 have a unified signal intensity; as Figure 4b As shown, based on Comparative Example 1, the Mn 2p signal in Comparative Example 2 is slightly weakened, while the Mn 2p signal in Example 1 is greatly weakened; as Figure 4c As shown, the Fe 2p signal in Example 1 is significantly enhanced; this indicates that the coating density of Example 1 in this application is significantly increased compared to Comparative Examples 1 and 2, which can effectively weaken the Mn 2p signal. Figure 5a As shown in the scanning electron microscope image of the first spinel-type material, lithium nickel manganese oxide, in Comparative Example 1, the particle surface is smooth and the particle edges are sharp. Figure 5b As shown in the image, the scanning electron microscope image of the positive electrode active material in Comparative Example 2 reveals a large number of small particles on the particle surface, indicating that the first spinel-type material, lithium nickel manganese oxide, has corundum-type Al2O3 particles on its surface. Figure 5c As shown in the scanning electron microscope image of the positive electrode active material in Example 1, it can be seen that the surface gloss of the positive electrode active material is darkened, the edges are somewhat blunted, and there are no obvious particles. Based on Figure 5a , Figure 5c This indicates that the first type of spinel-type material, lithium nickel manganese oxide, has a relatively dense coating layer (surface layer) on its surface. Figure 6a This is the energy scattering spectrum of the positive electrode active material in Example 1. Figure 6b This is a local cross-sectional energy scattering spectrum (Cross-section EDS) of the positive electrode active material of Example 1. Figure 6bAs can be seen from the data, including the core 1 and the surface layer 2, the Mn element in the first spinel-type material is uniformly distributed in the core 1, and the Fe element in the second spinel-type material, i.e. the surface layer 2, is uniformly and densely distributed on the surface of the first spinel-type material. This indicates that the surface layer 2 is uniform and dense on the outer surface of the core 1.
[0199] As shown in Tables 1 and 2, compared with Comparative Examples 1 and 2, the reversible capacity retention rate of the secondary batteries of Examples 1 to 24 of this application after being fully charged at 45°C and stored for 100 days is significantly increased. The amount of Mn deposited on the negative electrode plate of the secondary batteries after being fully charged and stored for 100 days is significantly reduced. This indicates that by coating or attaching a second spinel material to the surface of the first spinel material and controlling the molar ratio R2 of manganese in the second spinel material to be less than the molar ratio R1 of manganese in the first spinel material, the second spinel material is densely coated on the surface of the first spinel material, resulting in a lower Mn dissolution probability in the positive electrode active material and better storage performance of the secondary battery.
[0200] In Examples 1 to 5, the b2 in the second spinel-type material is 1, 1.5, 0.5, 0.5, and 0.3 respectively. The b2 in Example 2 is larger. The second spinel-type material coated on the surface of the positive electrode active material has a larger b2 and a higher total content of Mb elements such as Al, Nb, and Ti. This can stabilize the spinel structure, improve the stability of the second spinel-type material, reduce the dissolution of Mn ions, and improve the storage performance of the secondary battery.
[0201] Based on Examples 1, 15-18, Comparative Examples 1 and 2, coating with a second spinel-type material helps reduce Mn leaching from the positive electrode active material, reduces Mn deposition on the negative electrode, and improves the reversible capacity retention rate after storage. In Examples 1 and 15-18, as the surface layer mass percentage increases, the Mn deposition on the negative electrode shows a trend of first decreasing and then increasing, and the reversible capacity retention rate of the secondary battery after storage also shows a trend of first decreasing and then increasing; when the surface layer mass percentage reaches 10%, the Mn deposition on the negative electrode reaches its minimum, and the reversible capacity retention rate of the secondary battery after storage is also optimal.
[0202] Compared to Example 1, Examples 23 and 24 show a significant reduction in Mn deposition on the negative electrode sheet. The reversible capacity retention rate of the secondary battery after being fully charged at 45°C and stored for 100 days is relatively high. This indicates that the surface layer of the positive electrode active material includes a non-spinel material and a second spinel material. The mixture of the non-spinel material and the second spinel material can improve the density of the coating or attachment on the surface of the first spinel material, reduce the dissolution of Mn from the positive electrode active material, and improve the storage performance of the secondary battery.
[0203] The above description is merely an embodiment of this application and does not limit the patent scope of this application. Any equivalent structural or procedural transformations made using the content of this application's specification and drawings, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of this application.
Claims
1. A secondary battery, characterized in that, It includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive active material, which comprises: The core includes a first spinel-type material containing manganese, wherein the molar percentage of manganese in the first spinel-type material is R1, and R1 is greater than or equal to 0.1 and less than or equal to 0.
4. The surface layer covers or adheres to the outer surface of the core, and the surface layer includes a second spinel-type material, wherein the molar percentage of manganese in the second spinel-type material is R2, and R2 is greater than or equal to 0 and less than R1.
2. The secondary battery as described in claim 1, characterized in that, In the first type of spinel material, the sum of the molar percentages of nickel and manganese is R3, and R3 is greater than or equal to R1; in the second type of spinel material, the sum of the molar percentages of nickel and manganese is R4, and R4 is greater than or equal to R2; R4 is less than R3.
3. The secondary battery as described in claim 1 or 2, characterized in that, The first type of spinel material includes materials with the chemical formula Li x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1 The material has the following properties: 0.9≤x1≤1.2, 0≤y1≤0.3, 0.9≤x1+y1≤1.2, 1≤r1≤2, 0≤d1≤0.6, -0.1≤k1≤0.5, 0≤δ1≤0.5; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Me includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Cr, B, Al, Ga, In, Sc, Ti, V, Mn, Fe, Co, Y, Zr, Nb, Mo, Pb, Ta, W, lanthanides, C, Si, Ge, Sn, Pb, Sb, Bi, Te, P, and S; G includes one or more of F, Cl, Br, and I.
4. The secondary battery as described in claim 3, characterized in that, The second type of spinel material includes materials with the chemical formula Li x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The materials are 0≤x²≤2, 0≤y²≤2, 0.9≤x²+y²≤2, 0≤r²<2, 0≤d²≤0.6, 0≤a²≤2, 0≤b²≤2, 0≤r²<2, -0.1≤k²≤0.5, 0≤δ²≤2; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Ma includes one or more of Cr, Sc, V, Fe, Co, and Ni; Mb includes one or more of B, Al, Ti, Zr, Nb, Mo, Ta, W, Ce, Si, Te, and P; Mc includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Ga, In, Y, Pb, lanthanides, C, Ge, Sn, Pb, Sb, Bi, and S; G includes one or more of F, Cl, Br, and I.
5. The secondary battery as described in claim 4, characterized in that, r2 < r1; and / or, r2+d2<r1+d1; and / or, 0 ≤ r2 < 1; and / or, 0≤a2≤1; and / or, 0 < x² ≤ 1.2; and / or, 1≤b2≤2; and / or, Mb includes one or more of Zr, Nb, Mo, Ta, Te, and P.
6. The secondary battery according to any one of claims 1 to 5, characterized in that, The first type of spinel material includes one or more of lithium manganese oxide, lithium nickel manganese oxide, lithium nickel iron manganese oxide, lithium nickel iron aluminum niobium manganese oxide, and lithium nickel copper iron aluminum niobium manganese oxide; the second type of spinel material includes one or more of lithium nickel manganese oxide, lithium iron manganese oxide, lithium iron aluminum niobium titanium manganese oxide, lithium iron zirconium antimony manganese oxide, lithium aluminum niobium titanium manganese oxide, lithium cobalt aluminum niobium titanium manganese oxide, lithium iron aluminum niobium titanium manganese oxide, lithium magnesium aluminum niobium titanium manganese oxide, lithium copper titanium manganese oxide, magnesium iron manganese aluminum titanium oxide, lithium magnesium aluminum antimony oxide, and magnesium aluminum oxide.
7. The secondary battery according to any one of claims 1 to 6, characterized in that, The surface layer comprises a non-spinel material, which includes one or more of the following: inorganic substances with melting points below 1000°C, glucose, sucrose, fructose, amorphous carbon, and organic polymers.
8. The secondary battery as described in claim 7, characterized in that, The inorganic substances with melting points below 1000°C include one or more of lithium phosphate, lithium borate, boric acid, vanadium pentoxide, and boron oxide; and / or, The organic polymer includes one or more of polyacrylic acid, lithium polyacrylate, cyclohexanehexaphosphate, and phenolic resin.
9. The secondary battery according to any one of claims 6 to 8, characterized in that, The mass ratio of the non-spinel material to the second type of spinel material is greater than or equal to 0 and less than or equal to 2.
10. The secondary battery according to any one of claims 6 to 9, characterized in that, The mass ratio of the non-spinel material to the second type of spinel material is greater than or equal to 0.1 and less than or equal to 1.
11. The secondary battery according to any one of claims 1 to 10, characterized in that, Based on the total mass of the positive electrode active material, the surface layer accounts for 0.01% to 30% of the total mass.
12. The secondary battery according to any one of claims 1 to 11, characterized in that, The volume average particle size D of the positive electrode active material V 50 represents 1μm to 50μm.
13. A positive electrode active material, characterized in that, The positive electrode active material includes a core, which includes a first spinel-type material containing manganese. The molar percentage of manganese in the first spinel-type material is R1, where R1 is greater than or equal to 0.1 and less than or equal to 0.
4. The surface layer covers or adheres to the outer surface of the core, and the surface layer includes a second spinel-type material, wherein the molar percentage of manganese in the second spinel-type material is R2, and R2 is greater than or equal to 0 and less than R1.
14. The positive electrode active material as described in claim 13, characterized in that, In the first type of spinel material, the sum of the molar percentages of nickel and manganese is R3, where R3 is greater than or equal to R1; in the second type of spinel material, the sum of the molar percentages of nickel and manganese is R4, where R4 is greater than or equal to R2, and R4 is less than R3.
15. The positive electrode active material as described in claim 13 or 14, characterized in that, The first type of spinel material includes materials with the chemical formula Li x1 A y1 Me (2-r1-d1) Ni d1 Mn r1 O (4-k1-δ1) G δ1 The material has the following properties: 0.9≤x1≤1.2, 0≤y1≤0.3, 0.9≤x1+y1≤1.2, 1≤r1≤2, 0≤d1≤0.6, -0.1≤k1≤0.5, 0≤δ1≤0.5; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Me includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Cr, B, Al, Ga, In, Sc, Ti, V, Mn, Fe, Co, Y, Zr, Nb, Mo, Pb, Ta, W, lanthanides, C, Si, Ge, Sn, Pb, Sb, Bi, Te, P, and S; G includes one or more of F, Cl, Br, and I.
16. The positive electrode active material according to any one of claims 13 to 15, characterized in that, The second type of spinel material includes materials with the chemical formula Li x2 A y2 Mn r2 Ni d2 Ma a2 Mb b2 Mc (2-r2-a2-b2) O (4-k2-δ2) G δ2 The materials are 0≤x²≤2, 0≤y²≤2, 0.9≤x²+y²≤2, 0≤r²<2, 0≤d²≤0.6, 0≤a²≤2, 0≤b²≤2, 0≤r²<2, -0.1≤k²≤0.5, 0≤δ²≤2; Ma includes one or more of Cr, Sc, V, Fe, Co, and Ni; A includes one or more of Na, K, Rb, Cs, Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, and Cr; Mb includes one or more of B, Al, Ti, Zr, Nb, Mo, Ta, W, Ce, Si, Te, and P; Mc includes one or more of Be, Mg, Ca, Sr, Ba, Cu, Zn, Pt, Ag, Ga, In, Y, Pb, lanthanides, C, Ge, Sn, Pb, Sb, Bi, and S; G includes one or more of F, Cl, Br, and I.
17. The positive electrode active material according to any one of claims 13 to 16, characterized in that, The surface layer comprises a non-spinel material, which includes one or more of the following: inorganic substances with melting points below 1000°C, glucose, sucrose, fructose, amorphous carbon, and organic polymers.
18. An electrical appliance, characterized in that, Includes the secondary battery according to any one of claims 1 to 12, and / or the positive electrode active material according to any one of claims 13 to 17.